Blue moon ensemble simulation of aquation free energy profiles applied to mono and bifunctional platinum anticancer drugs. Issue 22 (26th June 2020) - Hirakawa, Teruo; Bowler, David R.; Miyazaki, Tsuyoshi; Morikawa, Yoshitada; Truflandier, Lionel A.
Abstract: Aquation free energy profiles of neutral cisplatin and cationic monofunctional derivatives, including triaminochloroplatinum(II) and cis‐diammine(pyridine)chloroplatinum(II), were computed using state of the art thermodynamic integration, for which temperature and solvent were accounted for explicitly using density functional theory‐based canonical molecular dynamics (DFT‐MD). For all the systems, the "inverse‐hydration" where the metal center acts as an acceptor of hydrogen bond has been observed. This has motivated to consider the inversely bonded solvent molecule in the definition of the reaction coordinate required to initiate the constrained DFT‐MD trajectories. We found that there exists little difference in free enthalpies of activation, such that these platinum‐based anticancer drugs are likely to behave the same way in aqueous media. Detailed analysis of the microsolvation structure of the square‐planar complexes, along with the key steps of the aquation mechanism, is discussed. Abstract : Monofunctional platinum(II) complexes with heterocyclic N‐donor ligand are promising anticancer drugs. As for bifunctional cisplatin, activation of the drug is taking place in the cellular media via aquation reaction. Aiming at clarifying this process, free activation energy profiles were investigated using DFT‐MD simulations along with blue moon ensemble thermodynamic integration based on a localized numerical atomic orbitals and pseudopotentials implementation.